Tissue Factor Coagulant Activity is Regulated by the Plasma Membrane Microenvironment - Yu, Yuanjie; Böing, Anita N.; Hau, Chi M.; Hajji, Najat; Ruf, Wolfram; Sturk, Auguste; Nieuwland, Rienk (Thrombosis and Haemostasis, 2018)
Background Tissue factor (TF) can be present in a non-coagulant and coagulant form. Whether the coagulant activity is affected by the plasma membrane microenvironment is unexplored.Objective This article studies the presence and coagulant activity of human TF in plasma membrane micro-domains.Methods Plasma membranes were isolated from human MIA PaCa2 cells, MDA-MB-231 cells and human vascular smooth muscle cells by Percoll gradient ultracentrifugation after cell disruption. Plasma membranes were fractionated by OptiPrep gradient ultracentrifugation, and the presence of TF, flotillin, caveolin, clathrin, protein disulphide isomerase (PDI), TF pathway inhibitor (TFPI) and phosphatidylserine (PS) were determined.Results Plasma membranes contain two detergent-resistant membrane (DRM) compartments differing in density and biochemical composition. High-density DRMs (DRM-H) have a density (ρ) of 1.15 to 1.20 g/mL and contain clathrin, whereas low-density DRMs (DRM-L) have a density between 1.09 and 1.13 g/mL and do not contain clathrin. Both DRMs contain TF, flotillin and caveolin. PDI is detectable in DRM-H, TFPI is not detectable in either DMR-H or DRM-L and PS is detectable in DRM-L. The DRM-H-associated TF (> 95% of the TF antigen) lacks detectable coagulant activity, whereas the DRM-L-associated TF triggers coagulation. This coagulant activity is inhibited by lactadherin and thus PS-dependent, but seemed insensitive to 16F16, an inhibitor of PDI.Conclusion Non-coagulant and coagulant TF are present within different types of DRMs in the plasma membrane, and the composition of these DRMs may affect the TF coagulant activity.
Keywords: tissue factor; coagulant activity; phosphatidylserine; plasma membrane; detergent-resistant membrane